An Assessment of fish production in Davao gulf for a sustainable use of fishery resources - Sambalod, Josie M.
This study was conducted to assess the fish production in Davao Gulf. Specifically, the study aimed to examine the trend in both commercial and municipal fishery production, the key determinants of production, and to evaluate the existence of a significant relationship , if any, between the fish production and its key determinants. Socio-economic and scientific-technical based data were used in the aanalysis. It was found that the total volume of fish production in Davao Gulf was increased annually by an average of 645.17 metric tons. Multiple linear regression analysis was used in texting the significance of the key determinants to fish production. Among the explanatory variables considered in the study, it was found that at 5% level of significance only the number of fishermen had a significant relationship with production. The study concludes that the sustainability of fishery resources was a function of intensive regulation among the user groups.